DIGITALIZATION AND INDONESIA'S MACROECONOMI RESILIENCE: AN EMPIRICAL VAR STUDY OF EXCHANGE RATE, INFLATION, FOREIGN DIRECT INVESTMENT AND DIGITAL ADOPTION - Septiana, Yuvi Putri; Shihab, Mochammad Qurais; Retnasih, Nora Ria (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study examines the relationship between digitalization and Indonesia's macroeconomic resilience, utilizing Fixed Broadband Subscriptions (FBS) and FBS per 100 people as indicators. Based on endogenous growth theory, which emphasizes the role of technology as a driver of long-term growth, this study uses the Vector Error Correction Model (VECM) approach, developed from the VAR concept by Sims (1980), to address endogeneity issues and examine short- and long-term relationships between variables. The research procedures include stationarity, cointegration, Granger causality, Impulse Response Function (IRF), and Variance Decomposition (VD) tests. The estimation results show that digitalization significantly impacts the exchange rate, inflation, and Foreign Direct Investment (FDI). In the short term, increased FBS encourages exchange rate appreciation but tends to weaken with increasing imports of digital devices, while the adoption of FBS per capita has a more stable positive impact. Digitalization also suppresses inflation by increasing distribution and production efficiency, although its contribution is relatively small compared to FDI. The impact of digitalization on FDI is twofold: FBS expansion attracts initial investment, but the sustainability of capital flows is heavily influenced by the quality of the digital ecosystem, regulations, and workforce readiness. Overall, these findings confirm that inclusive digitalization is a strategic tool for strengthening Indonesia's economic resilience to external shocks and building a foundation for more sustainable growth.